(untitled) (Eurasian Medical Research Periodical, 2023)
Ectrodactyly (polydactyly) is a genetic limb developmental disorder in which the hands or feet have an unusual shape and/or extra toes. This developmental disorder occurs during pregnancy when the limbs are still forming